Swedish electoral data: County council elections 1976 - Statistics Sweden (Statistics Sweden, 1989)
Election returns for all electoral districts in Sweden. Includes information on the total number of persons entitled to vote in the county council elections, and separately the number of immigrants who have not become citizens of Sweden, but were entitled to vote in this election according to a new law, number of persons who actually voted, and number of valid and invalid ballots respectively.

Valresultat för landstingsvalen 1796-2006 för alla valdistrikt i Sverige. Innehåller bland annat uppgifter om total andel röstberättigade, antal icke svenska medborgare som var röstberättigade enligt ny lag, valdeltagande, antal personer som röstade för olika alternativ, antal blanka röster samt andel giltiga och ogiltiga röster.
Svenska valdata: Landstingsvalen 1976
Keywords: elections; val; election data; valdata; Elections; Val; Social Sciences; Samhällsvetenskap